Establishing in vitro and in vivo Co-culture Models of Staphylococcus epidermidis and Enterococcus faecalis to Evaluate the Effect of Topical Fluoroquinolone on Ocular Microbes - Kim, Han Woo; Kim, Jiyeun Kate; Park, Indal; Lee, Sang Joon (Frontiers in Medicine, 2021)
Purpose: To establish in vitro and in vivo ocular co-culture models of Staphylococcus epidermidis and Enterococcus faecalis and study how various concentrations of moxifloxacin affect the survival of these two endophthalmitis-causing bacteria. Methods: Standard strains of S. epidermidis and E. faecalis were used. Color detection agar plates were used to differentiate their colonies. To establish in vitro and in vivo co-culture model, S. epidermidis and E. faecalis were co-cultured at different ratios and incubation periods. For the in vivo model, various volumes and concentrations of either a mono-culture or co-culture was inoculated into the lower conjunctival sac of rabbits. Finally, the established in vitro and in vivo co-culture models were exposed to moxifloxacin in various ways, and the effects were assessed. Results: When S. epidermidis and E. faecalis were mono-cultured in TSB, its growth peaked and plateaued at approximately 16 h and 6 h. When they were co-cultured, the growth peak of S. epidermidis was delayed, while the growth peak of E. faecalis was not changed. The number of E. faecalis in the co-culture was significantly higher than that in the mono-culture. Treatment of moxifloxacin for in vitro co-culture model rapidly decreased the number of S. epidermidis cells from 0.125 µg/mL. In contrast, the numbers of E. faecalis was not changed significantly up to 32 µg/mL moxifloxacin. In in vivo co-culture (mixed 1:1), S. epidermidis decreased in a similar pattern as shown in in vivo mono-culture and was barely detected at 24 h after inoculation. In contrast, E. faecalis increased up to 16 h and then decreased. When moxifloxacin was applied (0, 1, or 2 times) to this model, S. epidermidis decreased in proportion to the number of applications. In contrast, E. faecalis did not decrease, but rather increased in its number. Conclusions: The co-culture models of S. epidermidis and E. faecalis provided sufficient data to determine the effect of moxifloxacin eye drops on these bacteria. The moxifloxacin eye drops made E. faecalis dominant of the ocular surface.